Plagiarism knowledge, practice, reasons, and consequences: a cross-sectional study among Filipino nursing students - R. Ferrariz, Trixie Camille; Gargarita, Francis John P.; Debuque, Mary Bless G.; Dofitas, John Bernard A.; P. Espia, Dorothy Arlene Paz; Oducado, Ryan Michael F. (Institute of Advanced Engineering and Science, 2025)
Plagiarism is pervasive in academic environments and undermines nursing education’s integrity. Despite efforts to combat plagiarism, the problem persists, highlighting the need for a deeper investigation. This study determined the knowledge, practice, reasons, and perceived consequences of plagiarism among nursing students. A descriptive-correlational design was employed in a public nursing school in Iloilo, Philippines. An online survey using valid and reliable research instruments was administered among nursing students. Results revealed that while nursing students generally had high knowledge and low practice of plagiarism, one-fourth of students sometimes used tables, graphs, or pictures and copied information directly or in a slightly modified form without citing the sources. There was no significant relationship between the knowledge and practice variables. Common reasons cited by students for committing plagiarism were that many assignments had to be submitted quickly, the assignment to be done was very complicated, and there was a lack of time. Facing severe setbacks, serious consequences, and the risk of getting caught were viewed as potential consequences of plagiarism. This study underscores a possible gap between understanding the concept of plagiarism and implementing ethical academic practices, emphasizing the importance of institutions not just teaching about plagiarism but also revisiting some academic practices to identify the root causes of unethical behavior.